PENGUATAN KARAKTER PEDULI SOSIAL DALAM PEMBELAJARAN PAI SISWA KELAS VI SDN 1 SAMBA KATUNG KABUPATEN KATINGAN KALIMANTAN TENGAH - Taufik Rahman; Mazrur Mazrur; Abdul Gofur (Universitas Islam Lamongan, 2025)
Character education in schools is very important in forming students' dignified and socially aware personalities. One of the characters that needs to be instilled is social awareness, which can be implemented through Islamic Religious Education (PAI) subjects. This study aims to analyze the strengthening of social awareness characters in grade VI students of SDN 1 Samba Katung, Katingan Regency, Central Kalimantan through the material